Dexmedetomidine as Adjuvant in Scalp Nerve Block for Craniotomy: A Double-Blind Randomized Clinical Trial - Eka Nantha Kusuma, Putu; I Putu Pramana Suarjaya; Parami, Pontisomaya; IGAG Utara Hartawan; I Gusti Ngurah Mahaalit; I Putu Kurniyanta; Ida Bagus Krisna Jaya Sutawan; Sudiantara, Putu Herdita; I Made Gede Widnyana; Gde Agung Senapathi, Tjokorda (Jurnal Anestesiologi dan Terapi Intensif, 2025)
Introduction: Scalp nerve block (SNB) is an effective adjunct for attenuating hemodynamic responses and reducing postoperative pain in craniotomy. Dexmedetomidine (DEX), with its analgesic and anti-inflammatory properties, may enhance the quality of SNB. This study evaluated the effects of adding DEX to SNB on hemodynamic stability, postoperative pain, inflammatory response, and analgesic duration in craniotomy patients. Methods: A double-blind, parallel-group randomized clinical trial was conducted on 36 adult patients undergoing elective craniotomy (July–September 2025) at a tertiary hospital Denpasar. Participants received SNB using 0.375% ropivacaine (20 mL) with or without DEX 1 µg/kg under standardized general anesthesia. Outcomes included mean arterial pressure (MAP), Visual Analog Scale (VAS) scores at 12 and 24 hours, neutrophil-to-lymphocyte ratio (ΔNLR), and time to first rescue analgesic (TTFAR). Statistical analyses used mixed ANOVA and Mann–Whitney U tests. Ethical approval number was 2159/UN14.2.2.VII.14/LT/2025. Results: MAP was significantly lower in the DEX group at 10 minutes (Δ = 4.89 mmHg; 95% CI 1.62–8.16), 20 minutes (Δ = 4.83; 95% CI 1.57–8.10), 30 minutes (Δ = 3.67; 95% CI 0.40–6.94), and upon PACU arrival (Δ = 3.72; 95% CI 0.45–6.99) (all p < 0.05). Median VAS scores were significantly lower with DEX at 12 hours (1.50 vs 3.00; p < 0.001) and 24 hours (1.00 vs 2.00; p < 0.001). ΔNLR was reduced in the DEX group (−0.56 vs 3.08; p = 0.004). TTFAR was markedly prolonged (554 vs 257 minutes; p < 0.001). No adverse events were reported. Conclusion: Dexmedetomidine added to scalp nerve block enhances hemodynamic stability, reduces postoperative pain for up to 24 hours, suppresses early systemic inflammation, and prolongs analgesic duration in craniotomy without observed complications. DEX–SNB represents a beneficial component of multimodal analgesia in neuroanesthesia and may support enhanced recovery pathways